ChemInform Abstract: Unexpected Cyclization of Tritylamines Promoted by Copper Salt Through C—H and C—N Bond Cleavages to Produce Acridine Derivatives. Issue 12 (March 2015) - Morioka, Ryosuke; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
Abstract Treatment of the tritylamine substrates with [RhCl(cod)]2/Cu(O‐Ac)2 is known to produce 9‐aryl‐9H‐fluorene‐9‐amines.